Impact of exfoliated structure on the performance of electrospun SPEEK/cloisite nanocomposite membranes as proton exchange membranes for direct methanol fuel cell application. Issue 4 (August 2021) - Awang, N.; Yajid, M.A.M.; Jaafar, J.
Abstract: One of the key issues in the DMFC framework is methanol crossover. Surface modification is a promising approach to problem solving. A SPEEK/cloisite nanocomposite membrane exfoliated by electrospun is developed in this research. The membrane is prepared by immersing electrospun SPEEK/cloisite fibers mats in the SPEEK polymer matrix, which is half-solidated. The research addresses the effect of exfoliated morphology on the productivity of membranes. Compared to other sampling membranes like Nafion® 117, SP/e-spunCL15 with a completely exfoliated configuration has the best efficiency with a current density of 7.73 mAcm −2 and a power density of 1.18 mWcm −2 . Improved morphological, dimensional change properties and performance assign a well dispersed cloisite15A induced by the electrospinning technique to the membranes more effective for direct methanol fuel cell applications. Graphical Abstract: ga1 Highlights: Electrospinning is the new approach in fabricating proton exchange membranes. Exfoliated structure is important in improving performance of PEM. Exfoliated structure creates smaller path for methanol permeation process.